2017
DOI: 10.1111/pcn.12534
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the N400 component in relation to hypomanic personality traits in a word meaning ambiguity resolution task

Abstract: We found differences in semantic processing (i.e., detection of incongruence and semantic inhibition) in individuals with higher Social Vitality subscores. In the light of the literature, we discuss the notion that a semantic processing impairment could be a potential marker of vulnerability to BD, and one that needs to be explored further in this clinical population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The Social Vitality subscale estimates social potency and vivaciousness, but also reflects impulsivity traits ( 32 ). In our previous work conducted with ERPs on the same task, we found that the difficulty participants with higher HPS scores had handling the competition between different meanings of ambiguous words was related to modulation of the amplitude of the N400 component in frontal and frontocentral areas, and this modulation was in turn correlated with the HPS Social Vitality subscore ( 21 ). Taken together, these results provide evidence that high levels of hypomanic personality traits are associated with specificities in the processing of ambiguity resolution at the electrophysiological and neuroanatomical levels.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The Social Vitality subscale estimates social potency and vivaciousness, but also reflects impulsivity traits ( 32 ). In our previous work conducted with ERPs on the same task, we found that the difficulty participants with higher HPS scores had handling the competition between different meanings of ambiguous words was related to modulation of the amplitude of the N400 component in frontal and frontocentral areas, and this modulation was in turn correlated with the HPS Social Vitality subscore ( 21 ). Taken together, these results provide evidence that high levels of hypomanic personality traits are associated with specificities in the processing of ambiguity resolution at the electrophysiological and neuroanatomical levels.…”
Section: Discussionmentioning
confidence: 86%
“…The semantic ambiguity resolution task, derived from the task developed by Hoenig and Scheef ( 22 ), featured 90 auditory context sentences, each followed by a written target word. The material has already been described in detail elsewhere ( 21 ). Briefly, half the priming sentences ended with a homophone, and the context of the sentence pointed toward the homophone’s subordinate meaning (i.e., ambiguous condition), while the other half ended with a control word that was synonymous with the subordinate meaning of the homophone (i.e., unambiguous condition; see Table 2 for an example).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations